Perianal Median Raphe Cyst: A Rare Lesion with Unusual Histology and Localization - Betül Ünal; Cumhur İbrahim Başsorgun; Meryem İlkay Eren Karanis; Gülsüm Özlem Elpek (Case Reports in Dermatological Medicine)
Median raphe cysts present anywhere between the external urethral meatus and the anus. The cysts can occur at parameatus, glans penis, penile shaft, scrotum, or perineum. Perianal region is an extremely rare location for these lesions. Here we present a 50-year-old male patient who presented with a cystic, fluctuant lesion, located at 12 o’clock in perianal region. Microscopic examination revealed a cystic lesion with keratinized and nonkeratinized stratified squamous epithelium, pseudostratified ciliated epithelium, and scattered goblet cells. The final diagnosis of the lesion was median raphe cyst. Ciliated cells and perianal localization in median raphe cysts are extremely rare characteristics.